2023
DOI: 10.3390/jpm13030522
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Quality of Life in Treatment-Resistant Schizophrenia Patients Undergoing Avatar Therapy: A Content Analysis

Abstract: Avatar Therapy has a significant impact on symptoms, beliefs, and quality of life of patients with treatment-resistant schizophrenia. However, little is known about how these changes are implemented into their lives and to which aspects of their lives these improvements relate. Ten consecutive patients enrolled in an ongoing clinical trial were assessed using semi-guided interviews before as well as three months after Avatar Therapy. These encounters have been recorded and transcribed so that the discourse cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Pilot studies examining the effects of AT showed that patients with TRS improved by significantly lowering the frequency of persistent auditory hallucinations as well as the distress associated with these symptoms, with large effect sizes [31,32]. Moreover, this therapy also significantly improved their quality of life [33]. To better document and analyze the content of the immersive portions (dialogues between the avatar and the patient), two main qualitative studies were conducted.…”
Section: Current Innovation: Virtual Reality Therapymentioning
confidence: 99%
“…Pilot studies examining the effects of AT showed that patients with TRS improved by significantly lowering the frequency of persistent auditory hallucinations as well as the distress associated with these symptoms, with large effect sizes [31,32]. Moreover, this therapy also significantly improved their quality of life [33]. To better document and analyze the content of the immersive portions (dialogues between the avatar and the patient), two main qualitative studies were conducted.…”
Section: Current Innovation: Virtual Reality Therapymentioning
confidence: 99%